Between mutuality, autonomy and domination: rethinking digital platforms as contested relational structures. (18th August 2021) - Schüßler, Elke; Attwood-Charles, Will; Kirchner, Stefan; Schor, Juliet B
Abstract: This Special Issue advances a new understanding of digital platforms as dynamic and relational. An archetypal transaction platform, we argue, is comprised of three canonical social relationships which exist in tension with each other. The first is mutuality—the practices of sharing and reciprocity which animated the early days of the 'sharing economy'. The second is autonomy—representing the desire for freedom and independence attracting many earners to platforms. The third is domination—the exercise of power and control which drives many platform owners and managers. As we argue below, these three social relationships are present in varying degrees on all platforms. By conceptualizing platforms as contested relational structures, we aim to bridge prior attempts to classify 'what platforms are' with diverse empirical studies of 'what platforms do' in different contexts. In our view, platforms can do different things at the same time because they are different things at the same time.